PHARMACOLOGICAL EFFECTS OF THE SYNTHETIC ANALOGUE OF ANTIMICROBIAL PEPTIDE OF INDOLICIDIN 21 ON THE REGENERATION OF THERMAL WOUNDS IN THE EXPERIMENT - Viktor Lazarenko; Yuri Lyashev; Nikolay Shevchenko (Belgorod National Research University, 2017)
Introduction: Burn injuries in developed countries are among the most spread injuries of peacetime. The growth of resistance of microorganisms to existing antibiotics makes it necessary to develop some new generation antimicrobial drugs in the coming years. One possible way to solve the problem is to create drugs based on antibiotic peptides. Methods: There were studied the effects of the use of the synthetic analogue of indolicidin 21 on the processes of regeneration of thermal wounds, the systemic inflammatory response, the functional activity of neutrophils and macrophages, lipid peroxidation processes for IIIA-B degree burns and II-III degree frostbites in rats. Results: In the course of the study, we have established some stimulating effects of the synthetic analogue of the natural antimicrobial peptide indolicidin 21 on the processes of reparative skin regeneration after a local skin burn IIIA-B and a local frostbite of II-III degree, which are manifested in the acceleration of healing and prevention of purulent complications of thermal wounds. The use of the analogue of the indolicidin 21 has positive effects both on the functional activity of granulocytes of blood and macrophages, and on the systemic inflammatory reaction. The use of the synthetic analogue leads to an increase in the concentration of lipid peroxidation products in the blood plasma and skin supernatant throughout the experiment after a local burn, and up to 10 days after a local frostbite. The activity of antioxidant enzymes under the influence of the synthetic analogue of indolicidin was higher than the control values. Conclusion: The study has revealed that the use of synthetic analogue of indolicidin 21 is an effective method of pharmacological correction of reparative processes in the skin with thermal damage. It was also found that the most effective use of the synthetic analogue of the peptide was with the dose of 500 μg/kg.